EFFECT OF ULTRASONIC SCALING OF TEETH INVOLVED WITH PERIODONTAL DISEASE IN DOGS: A SCANNING ELECTRON MICROSCOPIC STUDY - Lacerda, Moacir Santos de; Alessi, Antonio Carlos [UNESP] (Univ Federal Uberlandia, 2015)
Scaling using ultrasonic dental equipment was performed on 20 teeth extracted from dogs with advanced periodontal disease, under clinical indication. The surgical extraction of the teeth, which already showed mobility, carried out by means of a lever, tried not to touch the radicular surface which would be assessed. The mesial surface of the cervical root region was used for verifying the effect of the ultrasonic scaling and the distal surface was maintained intact for control. After treatment, the teeth were sectioned, separating the region of interest, and these were fixed in glutaraldehyde, dried with a critical point dryer and metallized for observation under electronic scanning microscopy. The presence of plaque, biofilm and rod cells on the non-treated surface was quite characterized. On the surface submitted to treatment by ultrasound, it was possible to see areas with the removal of all the dental calculus, and areas with exposed naked dentine and showing open dentinal tubules. It was possible to observe also the occasional presence of bio-film and rod cells penetrating the dentinal tubules. No harm to the dentine was observed. Thus, ultrasonic scaling showed to be useful in the purpose of removing plaque and can be better developed. Future studies are necessary to establish a comparison with other methods of scaling.
Keywords: Dog; Periodontal disease; Scaling